A High Voltage Olivine Cathode for Application in Lithium‐Ion Batteries. Issue 2 (23rd December 2015) - Di Lecce, Daniele; Brescia, Rosaria; Scarpellini, Alice; Prato, Mirko; Hassoun, Jusef
Abstract: A new olivine composition (i.e., LiFe0.25 Mn0.5 Co0.25 PO4 ) is proposed as electrode material with increased energy density for application in lithium‐ion batteries. The new formulation increases the working voltage and induces different electrochemical behavior with respect to bare olivine materials based on Fe. The study provides deep insight into the features of the Fe 3+ /Fe 2+, Mn 3+ /Mn 2+, and Co 3+ /Co 2+ redox couples within the olivine lattice in terms of electrochemical activity, Li + transport properties, and Li‐cell behavior. The electrochemical characterization clearly reveals the voltage signatures corresponding to the various metals; however, the Mn 3+ /Mn 2+ process has higher intrinsic polarization with respect to Fe 3+ /Fe 2+ and Co 3+ /Co 2+ . This issue is efficiently mitigated by carbon coating the material, resulting in enhanced electrochemical performances. Abstract : Tune it up ! A new olivine composition (LiFe0.25 Mn0.5 Co0.25 PO4 ) is synthesized using a solvotermal approach and investigated for application in lithium‐ion batteries. The carbon‐coated material evidences the response of Fe 3+ /Fe 2+, Mn 3+ /Mn 2+, and Co 3+ /Co 2+ redox couples. The presence of the various metals is reflected in a higher working voltage of the cathode.